Hopfield multiuser detection of asynchronous MC-CDMA signals in multipath fading channels - Soujeri, E; Bilgekul, H (IEEE-Inst Electrical Electronics Engineers Inc, 2002)
Multiuser reception using Hopfield neural network (HNN) for asynchronous multicarrier code-division multiple access (MC-CDMA) in a multipath fading channel is investigated. We have shown that by the appropriate choice of HNN parameters from the channel state information, the HNN can collectively resolve the MPF effects and the multiple-access interference in the system.
Keywords: Hopfield neural network; MC-CDMA; multipath fading channel